Analisis Arus Bocor Isolator Porselen Tipe Piring Konduktor Tunggal terhadap Temperatur dan Kelembapan - JULIANDA, ANDRI; WALUYO (e-Proceeding FTI, 2024)
One of the important electrical equipment in the electric power system is an insulator that functions electrically as an insulation between live conductors and transmission towers. Because it is installed in an open space, environmental factors, such as temperature and humidity have a great influence on the insulator leakage current. Therefore it is necessary to investigate, by measuring the insulator leakage current, specifically for the type of porcelain plate, together with the parameters of the surrounding environment, and analyzing the results of these measurements using the correlation coefficient. The measurement results show that the value of the leakage current will increase when the humidity number is high. The lowest leakage current value is 106.5 μA and the highest leakage current value is 141.5 μA. From the results of the correlation efficiency analysis results show that the parameter that affects the increase in leakage current is humidity with a positive relationship of 0.766 (positive linear, high correlation). Abstrak Salah satu peralatan listrik yang penting dalam sistem tenaga listrik adalah isolator yang berfungsi secara elektris sebagai penyekat (isolasi) antara konduktor bertegangan dengan menara (tower) transmisi. Karena dipasang pada ruangan terbuka, faktor lingkungan, seperti temperatur dan kelembapan memiliki pengaruh besar terhadap arus bocor isolator. Oleh karena itu perlu diteliti, dengan melakukan pengukuran arus bocor isolator, khusus tipe piring porselen, bersama parameter lingkungan sekitar, serta menganalisis hasil pengukuran tersebut menggunakan koefisien korelasi. Hasil pengukuran menunjukkan bahwa nilai arus bocor akan meningkat pada saat angka kelembapan tinggi. Nilai arus bocor terendah 106,5 μA dan nilai arus bocor tertinggi 141,5 μA. Dari hasil analisis koefisien korelasi menunjukkan bahwa parameter yang mempengaruhi kenaikan arus bocor adalah kelembapan dengan hubungan positif sebesar 0,766 (linear positif, korelasi tinggi).